Phytochemical and Pharmacological Review of Cryptolepis sanguinolenta (Lindl.) Schlechter - Newman Osafo; Kwesi Boadu Mensah; Oduro Kofi Yeboah (Hindawi Limited, 2017)
Ethnopharmacological Relevance. Cryptolepis sanguinolenta is a scrambling thin-stemmed shrub found in Africa. Traditionally in West Africa, it is employed in the treatment of malaria, diarrhea, and respiratory conditions. This review discusses the traditional importance as well as the phytochemical, ethnomedical, pharmacological, and toxicological importance of this plant. Materials and Methods. Excerpta Medica Database, Google Scholar, Springer, and PubMed Central were the electronic databases used to search for and filter primary studies on Cryptolepis sanguinolenta. Results. The detailed review of various studies conducted on C. sanguinolenta and some of its constituents gives an important body of proof of its potential therapeutic benefits and also of its use as a source of lead compounds with therapeutic potentials. Conclusion. The review on C. sanguinolenta is important in identifying grey areas in the research on this medicinal plant and also provides comprehensive data thus far to continue research on this plant.